AB1201 Diversity in clinical manifestations of autoinflammatory syndromes in a french paediatric rheumatology referral center. (23rd January 2014) - Boiu, S.; Neven, B.; Compeyrot-Lacassagne, S.; Mouy, R.; Wouters, C.; Gattorno, M.; Quartier, P.
Abstract : Background: The autoinflammatory syndromes (AISs) include monogenic and polygenic disorders characterized by primary dysfunction of the innate immune system. Objectives: To describe the clinical spectrum, genetic background and therapy in a cohort of AIS patients followed in a reference Pediatric Rheumatology center. Methods: Medical records of AIS patients followed until November 2010 and entered in the Eurofever Registry were studied. Results: Fifty six patients were included: 17 CAPS, 4 TRAPS, 5 HIDS, 18 FMF, 6 CRMO, 2 SAPHO and 4 Behçet's Disease (BD). The median follow-up was 2 years (0-14 years). The male/female ratio was 20/36. The median age was 2.5 years at disease onset and 4 years at diagnosis. Family history was positive in 34% of patients. Clinical manifestations included fever (79%), musculoskeletal (77%), gastrointestinal (63%), mucocutaneous (61%), neurological (41%), ocular (34%), cardiorespiratory (13%), and genitourinary (2%) findings, lymphadenopathy with/or hepatosplenomegaly (16%) and growth impairment (25%). The main organ system manifestations were arthralgia (70%), abdominal pain (50%), urticarial rash (34%), headache (34%), conjunctivitis (16%), generalized lymph node enlargement (13%), and chest pain (9%). Complications/sequelae developed in 45% of patients and involved the musculoskeletal (25%), neurological (21%), gastrointestinal (11%) and ocular (7%) systems. Six patients presented with severe/unusual manifestations: neonatal peritonitis (1 CAPS), pancreatitis (1 TRAPS), acute glomerulonephritis (1 FMF), complicated Henoch-Schonlein purpura (1 FMF), peritoneal adhesions with intestinal occlusion (1 FMF), periorbital pain (1 CRMO) and cerebral thrombosis (1 BD). AISs were associated with other diseases in 2 patients (FMF/Hénoch-Schönlein purpura and CRMO/enthesitis-related arthritis). One mutant allele was found in 16/17 CAPS, 4/4 TRAPS and 4/18 FMF patients. Two mutant allelles were present in 5/5 HIDS and 11/18 FMF patients.The most used therapeutic agents were biologics (54%) (anakinra, canakinumab, etanercept, adalimumab), NSAIDs (48%), colchicine (45%) and corticosteroids (29%). Anti-interleukin-1 therapy and colchicine proved efficacy in CAPS and FMF patients, respectively. In addition, favorable responses demonstrated anti-interleukin-1 therapy in TRAPS, HIDS and colchicine-resistant FMF patients, as well as etanercept in TRAPS, HIDS and CRMO patients non-responsive to NSAIDs. Fifty seven% and 41% of patients were in complete and partial remission, respectively, at last visit. Conclusions: AISs in children are associated with a broad spectrum of manifestations. A detailed history, thorough review of clinical manifestations and molecular testing of specific causative genes can provide early and accurate diagnosis and institution of efficient therapy. Disclosure of Interest: None Declared